Analysis of the Effect of Slot Size and Shape On Microstrip Antenna 5G Band N40 Application - Rahmadani, Annisa’; Shofi Akbar, Fannush; Silk Moonlight, Lady (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
With the emergence of digital wireless communication technology, the fifth generation of LTE (Long Term Evolution) - 5G technology was developed to enhance faster data performance. For ensuring optimal execution of this technology, an antenna is required as a transmitter. Microstrip antenna is a low-cost and easy-to-manufacture antenna. Nevertheless, the drawback of microstrip antennas is their low gain. In this study, a microstrip antenna was designed by adding a slot to the patch for use in the 5G band N40 network. The antenna's dimensions were determined, and it was designed, simulated using software, fabricated, and measured. The measurement results were analyzed in conjunction with the simulation results. The study involved the design and testing of a microstrip antenna operating at 2.35 GHz. The antenna exhibited a S1.1 value of -21.2 dB, a VSWR value of 1.19, a gain value of 3.69 dBi, and a bandwidth value of 90.6 MHz. Additionally, a rectangular slot antenna was designed and tested, yielding a S1.1 value of -19.884 dB, a VSWR value of 1.225, a gain value of 3.707 dBi, and a bandwidth value of 91.7 MHz. Meanwhile, the most optimal circular slot antenna has a return loss value of -19.55 decibels, a voltage standing wave ratio value of 1.235, a gain value of 3.71 decibels, and a bandwidth value of 91.8 megahertz. The measurement results of the single patch microstrip antenna give a return loss S1.1 of -13.01 dB, VSWR of 1.48, gain of 4.3 dBi and bandwidth of 170 MHz. Then the best rectangular slot antenna has a return loss S1.1 of -16.22 dB, VSWR value of 1.37, gain value of 4.7 dBi and bandwidth value of 170 MHz. Meanwhile, the best circular slot antenna has a return loss S1.1 of -16.91 dB, a VSWR value of 1.34, a gain value of 6.7 dBi and a bandwidth value of 170 MHz.